Co-culture of BMSCs and HUVECs with simvastatin-loaded gelatin nanosphere/chitosan coating on Mg alloy for osteogenic differentiation and vasculogenesis - Qi, Hongfei; Wang, Kun; Li, Meng; Zhang, Yanni; Dong, Kai; Heise, Svenja; Boccaccini, Aldo R.; Lu, Tingli (International Journal of Biological Macromolecules, 2021)
Mg alloys are increasingly being investigated as a versatile and economical alternative for developing bone repair implants because of their high mechanical strength, wide availability, adjustable structure and properties. In this study, magnesium alloy WE43 is coated on both sides with gelatin nanosphere/chitosan (GNs/CTS), a coating enhanced by incorporating simvastatin (SIM). SIM-loaded GNs/CTS coated magnesium alloy can promote the osteogenic differentiation of bone mesenchymal stem cells (BMSCs). BMSCs and human umbilical vein endothelial cells (HUVECs) are co-cultured through transwell systems. The release of SIM from the coating is found to increase the secretion of chemokine and angiogenic factors from BMSCs, which promote the migration and tube formation of HUVECs, respectively. Bone morphogenetic protein secreted by HUVECs is seen to increase by the release of SIM from the coating, promoting the osteogenic differentiation of BMSCs. The secretion of chemokines from HUVECs promote the migration of BMSCs. The coated magnesium alloy substrate loaded with SIM is found to regulate the osteogenic differentiation of BMSCs. The study of the paracrine interaction between BMSCs and HUVECs proves that the applied coating promotes both osteogenic differentiation and vascularization, thus demonstrating a new approach for the design of bone repair materials based on magnesium alloys.
CRIS-Team WoS Importer:2022-01-14